Is Dental Interventions Safe During Pregnancy - Abderahman, Mogahid; Elsanousi Mohamed, Mohamed (Gezira Journal of Health Sciences, 2011)
Objectives :  To investigate the safety of tooth extraction and other dental interventions during pregnancy. Methods : pregnant ladies with dental problems were seen by an obstetrician and a dentist. Simple cases were treated medically. Severe cases were identified. When surgical intervention was indicated due to abscess formation or disturbance of sleep, patient consent was taken and the necessary treatment was performed. A contact number was given to each patient and there addresses were taken. All treated patient were asked to report seven days latter for follow up of the dental condition and the pregnancy wellbeing. Results : This study involved 97 pregnant ladies, in different gestational ages, 50.5% of them were in the first trimester. Patients from urban area were 65.9%. The population of this study included patients with pregnancy order up to 8 however 23.7% of them were primigravidae. Some of these ladies (30.0%) gave past history of previous pregnancy complications. Each patient presented with more than two symptoms of the following: pain, disturbance of sleep, difficulty in food chewing, bleeding from the gum and earache. All patients had clinical evidence of infection either pulpitis, gingivitis or both. The main underlining problem of these participants was tooth caries. The surgical dental interventions included; tooth extraction, scaling, filing and root canal treatment. Conclusion The dental intervention during pregnancy using local anaesthesia is safe. The severe pain, difficulty of feeding and disturbance to sleep due oral/dental diseases may cause more danger to mother and her fetus than dental intervention.